In vitro Propagation of Ziziphus nummularia - Mathur, Nishi; Ramawat, K G; Sonie, K C (Annals of Arid Zone, 2016)
An ill vitro method for mass multiplication of ziziphus nummulorio, a highly drought resistant shrub of the Indian Desert, has been developed. Maximum and the best induction of multiple shoots (15-20) was in the explants from shoot tip, closely followed by that of cotyledonary node (10-15), nodal region (8-10) and hypocotyl (6-8) on Murashige and Skoog's (MS) medium containing.2.5 mgL-1kinetin (kn). These ill vitro raised shoots were excised and cultured on same but fresh medium for further multiplication. In addition original explants were also repeatedly subcultured on the fresh medium to obtain new shoots. Rooting in these isolated shoots from both the original explant and induced shoots could be induced by placing them for 12h on filter paper bridge in White's liquid medium containing 8.0 mgL-1.Indole Butyric acid (IBA). Thereafter, the shoots were transferred to agar-gelled hormone free White's medium. Regenerated plants were hardened and transferred to the pots.